EXTH-49. THERAPEUTIC EFFICACY OF ENGINEERED, HYDROGEL ENCAPSULATED BIMODAL MSC IN GLIOBLASTOMA STRATIFIED ON CELL SURFACE RECEPTOR EXPRESSION. (11th November 2019) - Bhere, Deepak; Hugh Choi, Sung; van de Donk, Pim; Khalsa, Jasneet; Hope, David; Gortzak, Kiki; Kunnummal, Amina; Reinshagen, Clemens; Ling, Huan; Vasdev, Neil; Ibn Essayed, Walid; Golby, Alexandra; et al.
Abstract: Engineered stem cell therapeutics present a promising therapeutic strategy for glioblastoma (GBM). However, their clinical translation in GBM patients is limited due to lack of mouse models that mimic clinical GBM scenario, dearth of stratification techniques for target cohorts and safety concerns. In this study, we have validated the potential of stratifying therapy responders based on a circulating tumor cell screen and developed a unique "off-the-shelf" cell surface receptor targeted engineered bi-functional mesenchymal stem cell (MSC) for resected GBMs. We created a dual promoter self-inactivating lentiviral vector plasmid encoding death receptor (DR4/5) ligand (DRL ), the tumor specific therapeutic agent and the prodrug-converting enzyme, herpes simplex virus-thymidine kinase (HSV-TK) and engineered clinical grade human bone marrow derived MSC to express the bi-modal therapeutic. We show that hyaluronic acid (HA) hydrogel encapsulated bimodal MSC are retained in the tumor resection cavity and have significant therapeutic efficacy in vitro and in vivo in mice bearing patient derived GBM tumors following DR4/5 stratification by circulating tumor cells in the blood and GBM surgical resection. We also show that fate of engineered MSC can be tracked by PET imaging and activation of pro-drug, HSV-TK enhances the therapeutic efficacy of MSC and results in their elimination post-tumor treatment. Our study reveals that local delivery of hydrogel encapsulated engineered MSC has therapeutic benefits; circumvents concerns of bio-distribution, increases on-site retention and permits tumor-selective migration. Based on this data, we are preparing for a first-in-human study of a hydrogel encapsulated engineered allogeneic MSC product, in primary GBM patients.